2008
DOI: 10.1017/s0265021508004511
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the i-gel airway in 300 patients

Abstract: Tetzlaff J. Atrial fibrillation after ondansetron for the prevention and treatment of postoperative nausea and vomiting: a case report. Can J Anesth 2003; 50(3): 229-231. 5. Higgins DJ, Bunker NJ. Dolasetron and peri-operative cardiac arrhythmia. Anaesthesia 2005; 60: 936-937. 6. Thompson A, Balser JR. Perioperative cardiac arrhythmias. Br J Anaesth 2004; 93: 86-94. 7. Mitterschiffthaler G, Putz G. Supraventricular tachycardia and ST segment depression after intravenous administration of tropisetron.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
44
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 3 publications
7
44
1
1
Order By: Relevance
“…), and this finding is in agreement with the results of Trivedi [17], Van Zundert [11], Bamgbade [18] and Radhika [19] previously discussed.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…), and this finding is in agreement with the results of Trivedi [17], Van Zundert [11], Bamgbade [18] and Radhika [19] previously discussed.…”
Section: Discussionsupporting
confidence: 93%
“…Bamgbade and colleagues [18] reported that the I-gel Rehab Abdel Raof Abdel Aziz and Yasser Mohamed Osman: Comparison of I-gel with Baska Mask Airway for Controlled Ventilation in Obese Patients Undergoing Ambulatory Surgery: A Prospective Randomized Trial could be inserted within 5 seconds in 290 out of 300 patients, but they did not specify how insertion time was defined. Radhika, et al [19] in their study, compared LMA-S versus Igel in 42 patients were randomly divided into two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have reported a median insertion time for the i-gel ranging from 5 to 15 sec (14,16,18).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous previous studies of these airway devices have demonstrated their easy, reliable insertion and low morbidity rate. (3)(4)(5)(6)(7) However, comparative studies involving all three aforementioned airway devices are lacking. One study testing the three devices used the laryngoscope-guided and gastric tubeguided methods of insertion, while another was conducted on paralysed, ventilated patients undergoing laparoscopic surgery.…”
Section: Introductionmentioning
confidence: 99%